The influence of plyometric training volume varied by exercise sets on lower-body explosive power - Papadakis, Z.; Grandjean, P. W. (International Journal of Sports Science, 2015)
Training volume and the number of sets for developing lower body explosive power are important considerations for plyometric training. The purpose of this study was to compare training volume differing in number of sets in a 8-week program on field-based measures of lower-body explosive power. We hypothesized plyometric training would enhance lower body explosive power in a dose-dependent manner in which a 4-set program would result in greater power improvements than a 2-set program. Seventy-two recreational exercisers were randomly assigned to one of 3 groups: 2-set, 4-set or non-plyometric control. Controls exercised ad libitum with the exception of any plyometric exercise. Training by experimental groups included weighted static jumps (SJ) and countermovement jumps (CMJ) using heavy and light loads, under a supervised and periodized program for 3 d/wk over 8 wks. Heavy loads were ramped up by 10% of one-repetition maximum (1RM) each week starting from 60% of 1RM, followed by a light load of 30% of 1RM for 8 repetitions for the first 4 wks of training. During the last 4 wks, the heavy loads were ramped down by 10% of 1RM each week starting from 90% of 1RM. The executed repetitions for the heavy loads for each week and each work-out day were periodized from 4 to 50 repetitions. Lower-body power was measured before and after using a commercial-available contact mat that recorded the ground reaction forces. The dependent variables were vertical jump height (H) and power (PW) of SJ and CMJ. One-way analyses of variance with paired post-hoc analysis on mean post-pre differences were employed to determine significant effects (p p = 0.0099), SJ-PW (p = 0.0208), CMJ-H (p = 0.0037), CMJ-PW (p = 0.0037) were all greater in 4-set group when compared to 2-set and control groups. The 2-set group did not differ from the control in any of the dependent variables. Plyometric training does not always improve explosive power. A periodized resistance plyometric program varied by exercise sets demonstrated that a greater training volume is necessary for developing lower-body explosive power. An effective way to increase plyometric training is to increase the number of sets.